2022
DOI: 10.3389/fnhum.2022.859519
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Modulation Index on Frequency-Modulated Steady-State Visual Evoked Potentials

Abstract: Based on increased user experience during stimulation, frequency-modulated steady-state visual evoked potentials (FM-SSVEPs) have been suggested as an improved stimulation method for brain-computer interfaces. Adapting such a novel stimulation paradigm requires in-depth analyses of all different stimulation parameters and their influence on brain responses as well as the user experience during the stimulation. In the current manuscript, we assess the influence of different values for the modulation index, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Other work showed that this is also feasible by combining frequencies at different stimulus attributes to obtain a multi-modal stimulus, i.e., the combination of the luminance flicker with color flicker [69,72] or with motion [30,80]. Also, frequency and amplitude modulation are shown to be feasible and could use the higher frequencies of the flicker-free band [26,32,65].…”
Section: Frequencymentioning
confidence: 99%
“…Other work showed that this is also feasible by combining frequencies at different stimulus attributes to obtain a multi-modal stimulus, i.e., the combination of the luminance flicker with color flicker [69,72] or with motion [30,80]. Also, frequency and amplitude modulation are shown to be feasible and could use the higher frequencies of the flicker-free band [26,32,65].…”
Section: Frequencymentioning
confidence: 99%